INCREASING THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT BY USING PICTURE STRATEGY AT THE EIGHTH GRADE OF SMP NEGERI 1 GIDO - WARUWU, PONIRIA; LAOLI, ADIELI; HAREFA, TRISMAN; DAELI, HIDAYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Writing is the important skill that must be master by the students. Writing is also about the skill of a writer to communicate the information to the reader or group of readers. Writing becomes an important aspect in language learning. By writing, the students can share information and ideas in the written text. They can share to each other about what they think and feel about people, ideas, issues, and events in the written text. The students will write their assignments that may be one paragraph or several paragraphs, and they will also write the answers for tests and exams that may be a few sentences, a paragraph or two, or a complete essay in written form. The purpose of the research is to Increase the Students’ Ability in Writing Descriptive Text by Using Picture Strategy at the Eighth Grade of Smp Negeri 1 Gidowhich the total numbers of the students was 20 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, evaluation sheet and field note. In the second meeting of cycle II, the researcher obtained the improvement of students, who achieved the Minimum Competence Criterion (63). there were 2 (10%) students who got score among 85-100 classified as “Very Good”, 6 (30%) students got score among 74-84 classified as “Good”, 12 (60%) no one students who reached the “Less” and no one students who reached the “Fail ”. In Cycle II the average was 83, the highest mark was 100 and the lowest was 63. It implies that the students’ ability in write descriptive text increase in cycle II. ABSTRAKMenulis merupakan keterampilan penting yang harus dikuasai oleh siswa. Menulis juga merupakan keterampilan seorang penulis untuk mengkomunikasikan informasi kepada pembaca atau sekelompok pembaca. Menulis menjadi aspek penting dalam pembelajaran bahasa. Dengan menulis, siswa dapat berbagi informasi dan ide dalam teks tertulis. Mereka dapat saling berbagi tentang apa yang mereka pikirkan dan rasakan tentang orang, ide, isu, dan peristiwa dalam teks tertulis. Siswa akan menulis tugas mereka yang mungkin berupa satu paragraf atau beberapa paragraf, dan mereka juga akan menulis jawaban untuk tes dan ujian yang mungkin berupa beberapa kalimat, satu atau dua paragraf, atau esai lengkap dalam bentuk tertulis. Tujuan dari penelitian ini adalah untuk Meningkatkan Kemampuan Siswa dalam Menulis Teks Deskriptif dengan Menggunakan Strategi Gambar di Kelas VIII Smp Negeri 1 Gido yang jumlah siswanya adalah 20 orang. Penelitian ini dilakukan dengan menggunakan desain Penelitian Tindakan Kelas (PTK). Penelitian ini diterapkan dalam dua siklus. Setiap siklus terdiri dari perencanaan, tindakan, observasi, dan refleksi. Instrumen yang digunakan peneliti untuk mengumpulkan data adalah lembar observasi, lembar evaluasi dan catatan lapangan. Pada pertemuan kedua siklus II, peneliti memperoleh peningkatan siswa, yang mencapai Kriteria Kompetensi Minimal (63). Ada 2 (10%) siswa yang mendapat nilai antara 85-100 yang tergolong “Sangat Baik”, 6 (30%) siswa mendapat nilai antara 74-84 yang tergolong “Baik”, 12 (60%) tidak ada siswa yang mencapai “Kurang” dan tidak ada siswa yang mencapai “Tidak Lulus”. Pada Siklus II rata-rata adalah 83, nilai tertinggi adalah 100 dan terendah adalah 63. Ini menyiratkan bahwa kemampuan siswa dalam menulis teks deskriptif meningkat pada siklus II.